Cost-utility analysis of combination medical therapies in chronic coronary syndrome: a comparative study using real-world and patient-level data from Iran - Fatemeh Soleymani; Parham Sadeghipour; Majid Davari; Abbas Kebriaeezadeh; Behzad Fatemi; Mohammad Reza Maracy; Nasim Naderi; Saman Zartab (BMJ Open)
Objectives The main objective was to evaluate the cost-effectiveness of various medical therapy combinations in managing chronic coronary syndrome (CCS) in Iran, based on real-world and patient-level data.Design A cost-utility analysis employing a Markov model was conducted using data from a retrospective cohort study.Setting The study was conducted in the healthcare setting of Iran, focusing on primary and secondary care.Participants Patients with CCS were included in the study. Numbers entering and completing the study were reported, with clear definitions of selection, entry and exclusion criteria.Interventions All combinations of recommended medical therapies for CCS were permitted. Ultimately, taking into account the sample size and study power, a comparison was made between the combination therapy of β-blockers (BB), long-acting nitroglycerin (LAN), aspirin (ASA) and statin versus the group receiving only BB, ASA and statin.Primary and secondary outcome measures The primary outcome measure was the incremental cost-effectiveness ratio, along with an initial evaluation of disability-adjusted life-years (DALYs) and costs related to the interventions.Results The BB/LAN/ASA/statin combination was cost-saving and effective, averting 0.02 DALYs and saving $172 compared with BB/ASA/statin. This combination was cost-effective in over 97% of the probabilistic sensitivity analysis results.Conclusions Incorporating LAN into the combination therapy of BB, ASA and statin is cost-effective in Iran. This finding provides evidence for policymakers on resource allocation in low-income countries.